2013
DOI: 10.1128/jvi.00197-13
|View full text |Cite
|
Sign up to set email alerts
|

Immature and Mature Dengue Serotype 1 Virus Structures Provide Insight into the Maturation Process

Abstract: Dengue virus is a major human pathogen that has four serotypes (DENV1 to -4). Here we report the cryoelectron microscopy (cryo-EM) structures of immature and mature DENV1 at 6-and 4.5-Å resolution, respectively. The subnanometer-resolution maps allow accurate placement of all of the surface proteins. Although the immature and mature viruses showed vastly different surface protein organizations, the envelope protein transmembrane (E-TM) regions remain in similar positions. The pivotal role of the E-TM regions l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(187 citation statements)
references
References 30 publications
2
183
2
Order By: Relevance
“…A recent cryo-EM study of mature DENV2 virions at high resolution (3.5 Å) revealed that several residues at the N-terminal loop of M protein (prM protein positions 91-110) interact with domain II residues of E protein (34). These interactions were also shown by another cryo-EM study of mature and immature DENV1 virions at 4.5 and 6 Å resolution, respectively (63). Based on these observations and previous structural studies of prM/E proteins and E protein at pre-and postfusion states, a model of maturation was proposed (33, 34, 56, 64 -66).…”
Section: Discussionmentioning
confidence: 69%
“…A recent cryo-EM study of mature DENV2 virions at high resolution (3.5 Å) revealed that several residues at the N-terminal loop of M protein (prM protein positions 91-110) interact with domain II residues of E protein (34). These interactions were also shown by another cryo-EM study of mature and immature DENV1 virions at 4.5 and 6 Å resolution, respectively (63). Based on these observations and previous structural studies of prM/E proteins and E protein at pre-and postfusion states, a model of maturation was proposed (33, 34, 56, 64 -66).…”
Section: Discussionmentioning
confidence: 69%
“…Superposition of the E proteins of DENV4 strain SG/ 06K2270DK1/2005 with DENV2 strain New Guinea C (30) and DENV1 strain PVP159 (19) does not show significant structural differences (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…So far, cryo-EM structures of the mature DENV1 (19) and DENV2 (20) are solved to 4.5-Å and 3.6-Å resolutions, respectively. Here we present the structure of mature DENV4 at a 4.1-Å resolution.…”
mentioning
confidence: 99%
“…In the infected cell, newly synthesized immature DENV virions bud into the ER lumen, where the pH is neutral. These particles contain 180 copies of a heterodimer of E with the precursor membrane glycoprotein prM at their surface 19,20 . As they are subsequently transported to the external medium across the Golgi apparatus, where the pH is acidic, the interaction with prM protects E from undergoing a premature acid--induced fusogenic conformational change 1 .…”
Section: Igkv3--11 (Ede1 C8 the Patient Appeared To Have A Primary mentioning
confidence: 99%